ANALISIS TIPIKAL RUMAH DI KOTA BENGKULU DAN KESESUAIAN DENGAN RUMAH TAHAN GEMPA - Fepy Supriani (Universitas Bengkulu, 2019)
Houses in the city of Bengkulu has several typical, both technical and non-walls house technical, semipermanent houses an d wooden houses. In some earthquakes that occured in the city of Bengkulu, the damage most occur in homes walss. A typical home built to include permanent and non permanent home that can be characterized based on the type of foundation, walls, strengthening structure and type of roof. This determines the typical damage caused by earthquake. The analysis was performes on 200 samples of homes in the city of Bengkulu using the method of observation and survey instrument interviews with written and directed. The result show that many typical houses in Bengkulu is home walls (89%) using continuous foundation stone (67.10%) and zinc roof coverings (65.80%). While strengthhening the structure used standard (Sloof 71.6%, 40.65%) and the column or beam around the ring either 50.32%), although the typical house has indicated the implemnentation of retrofitting structure not taking into account the buliding to earthquake or follow the requirements of earthquake resistant buildings, the use of tin roof was according to house quake-prone region.